Islamic Value-Based Digital Storytelling in Persuasive Messages on Social Media for Crowdfunding Organizations (Narrative Analysis of Instagram Account @Actforhumanity) - Satriaji, Afif Zuhdi; Destrity, Nia Ashton (Advances in Social Sciences Research Journal, 2024)
This research aims to analyze narrative digital storytelling based on Islamic values created by the Instagram account @actforhumanity. The researchers use a narrative analysis method within a constructivist paradigm, focusing on posts containing photos, videos, and captions that include Islamic values, characterization, emotion, and setting elements. The study covers posts from October 1, 2021, to January 20, 2022. The research identifies ten programs conducted by the Aksi Cepat Tanggap team. Two characterization methods were found: Aksi Cepat Tanggap as the hero helping victims and descriptions of the problems faced by victims. The study identifies thirteen types of settings, with citizen residences, refugee camps, and open spaces being the most dominant. Eleven emotions were identified, with sadness, compassion, and joy being the most prevalent. Seventeen kinds of Islamic values were used to build narratives, with the values of caring, charity, and helping each other being the most prominent.